Analisis Pengaruh Pajak Penjualan Atas Barang Mewah (PPnBM) Terhadap Daya Beli Konsumen Kendaraan Bermotor - Liza Asri; Uzlah Hansel Bahrin Hasibuan; Widiya Indah Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze the effect of sales tax on luxury goods (PPnBM) on consumers purchasing power to buy motorized vehicles. The research method used is a literature study by reviewing literature related to the concept of tax, PPnBM, consumer purchasing power, and the characteristics of motorized vehicles. The research results show that PPnBM has a negative effect on consumer purchasing power because it increases the costs that must be borne when purchasing motorized vehicles. Factors such as income and price influence consumer purchasing power. PPnBM is imposed on certain vehicles according to their categorization and rates, and the calculation uses the tax base. This research concludes that the imposition of PPnBM has an impact on reducing consumers ability to purchase motorized vehicles because it reduces purchasing power. Therefore, it is necessary to evaluate the imposition of PPnBM on consumers.